Healing Process in Rat with Burns after Feeding a High Protein Nano Liquid Food Formula from Catfish-Moringa - N.A. Shofiyyatunnisaak; Clara M. Kusharto; Faisal Anwar (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Burn injury is severe trauma that is mainly caused by fire that affects in various organ systems. The metabolic response caused by burn inury is catabolism of energy, protein, and lipid, so a high quality nutrition with high bioavailability is needed to accelerate wound healing process. The purpose of this study was to analyze the effect of food intervention of liquid food formula from catfish (Clarias gariepinus)-moringa (Moringa oleifera) that have been processed by nanoparticle technology and the effect of body weight and wound healing process through the number of fibroblasts in rats with burn. This study used an experimental design with completely randomized design with ethical number 203-2021 IPB. The samples were 3 month old male Sprague Dawley rats weighing 200-300 grams. There are 6 intervention treatments: control group (aquades), commercial liquid food formula 30%, non-nano liquid food formula 15%, non-nano liquid food formula 30%, nano liquid food formula 15%, and nano liquid food formula 30%. The intervention was carried out for 14 days. Statistical analysis for the difference test used One Way ANOVA. The body weight of rats continued to decrease from day 0,6 to 15. There was no significant difference between groups in the average body weight of rats on days 0,6, and 15 (p-value>0,05). There was a tendency that nano liquid food formula was accelerated the wound healing process in burn rats after 14 days of intervention, but no significantly (p-value>0,05).